2017
DOI: 10.1002/ana.24881
|View full text |Cite
|
Sign up to set email alerts
|

Glial fibrillary acidic protein immunoglobulin G as biomarker of autoimmune astrocytopathy: Analysis of 102 patients

Abstract: GFAPα-IgG, when detected in CSF, is highly specific for an immunotherapy-responsive autoimmune CNS disorder, sometimes with paraneoplastic cause. Ann Neurol 2017;81:298-309.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

37
677
7
16

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 438 publications
(737 citation statements)
references
References 34 publications
37
677
7
16
Order By: Relevance
“…Necrotizing meningoencephalitis and granulomatous meningoencephalitis are idiopathic inflammatory diseases of the central nervous system associated with GFAP antibodies in dogs, demonstrating inflammatory cell infiltration of the perivascular area and brain parenchyma by mixed populations of CD3 + T cells, B lymphocytes, plasma cells, and macrophages in almost equal ratios [7, 8]. Our current results support the hypothesis that T lymphocytes interact with B cells and other inflammatory components of the immune system (microglia, macrophages, and antibody secretion by plasma cells), contributing to the pathogenesis of GFAP neurological autoimmunity [2]. …”
Section: Discussionsupporting
confidence: 77%
“…Necrotizing meningoencephalitis and granulomatous meningoencephalitis are idiopathic inflammatory diseases of the central nervous system associated with GFAP antibodies in dogs, demonstrating inflammatory cell infiltration of the perivascular area and brain parenchyma by mixed populations of CD3 + T cells, B lymphocytes, plasma cells, and macrophages in almost equal ratios [7, 8]. Our current results support the hypothesis that T lymphocytes interact with B cells and other inflammatory components of the immune system (microglia, macrophages, and antibody secretion by plasma cells), contributing to the pathogenesis of GFAP neurological autoimmunity [2]. …”
Section: Discussionsupporting
confidence: 77%
“…In the present study, we described 7 patients with GFAP antibodies in their CSF, which has been defined as GFAP astrocytopathy in recent reports [1,2] . Although this study had a small sample number, we are the first to describe the long-term treatment and evolution in Chinese patients.…”
Section: Discussionmentioning
confidence: 75%
“…The Mayo clinic study reported that patients with GFAP astrocytopathy responded well to steroids or aggressive immunosuppression [1,2] . However, evidencebased therapy of GFAP astrocytopathy is absent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations